Geography : a very short introduction - Matthews, John A. (John Anthony), 1947- (Very short introductions, 2008)
Modern geography has come a long way from its roots in simply mapping and naming the regions of the world. Spanning both physical and human geography, the discipline today bridges the divide between the sciences and humanities, and between the environment and our society. This book reveals how and why.